Oxygenation, ventilation, and airway management in out-of-hospital cardiac arrest: a review - Henlin, Tomas; Michalek, Pavel; Tyll, Tomas; Hinds, John D; Dobias, Milos (BioMed research international, 2014)
Recently published evidence has challenged some protocols related to oxygenation, ventilation, and airway management for out-of-hospital cardiac arrest. Interrupting chest compressions to attempt airway intervention in the early stages of OHCA in adults may worsen patient outcomes. The change of BLS algorithms from ABC to CAB was recommended by the AHA in 2010. Passive insufflation of oxygen into a patent airway may provide oxygenation in the early stages of cardiac arrest. Various alternatives to tracheal intubation or bag-mask ventilation have been trialled for prehospital airway management. Simple methods of airway management are associated with similar outcomes as tracheal intubation in patients with OHCA. The insertion of a laryngeal mask airway is probably associated with worse neurologically intact survival rates in comparison with other methods of airway management. Hyperoxemia following OHCA may have a deleterious effect on the neurological recovery of patients. Extracorporeal oxygenation techniques have been utilized by specialized centers, though their use in OHCA remains controversial. Chest hyperinflation and positive airway pressure may have a negative impact on hemodynamics during resuscitation and should be avoided. Dyscarbia in the postresuscitation period is relatively common, mainly in association with therapeutic hypothermia, and may worsen neurological outcome.
Keywords: oxygenoterapie; urgentní zdravotnické služby; zajištění dýchacích cest; Out-of-Hospital Cardiac Arrest; Oxygen Inhalation Therapy; Emergency Medical Services; lidé; umělé dýchání; Heart Arrest; kombinovaná terapie; Combined Modality Therapy; Respiration, Artificial; srdeční zástava; Airway Management; zástava srdce mimo nemocnici; Humans